2017
DOI: 10.3758/s13414-017-1437-z
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay of visuospatial and audiotemporal dominance: Evidence from a multimodal kappa effect

Abstract: When participants judge multimodal audiovisual stimuli, the auditory information strongly dominates temporal judgments, whereas the visual information dominates spatial judgments. However, temporal judgments are not independent of spatial features. For example, in the kappa effect, the time interval between two marker stimuli appears longer when they originate from spatially distant sources rather than from the same source. We investigated the kappa effect for auditory markers presented with accompanying irrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…To fully understand human processing of time and space, multisensory studies are needed. It was already shown that cross-modality tau (Kawabe et al, 2008 ) and kappa (Bausenhart & Quinn, 2018 ) effects can be observed when temporal information is presented auditorily and spatial information visually. Also, research in related areas, for instance, on the representational momentum (the final location of a disappearing moving object is perceived to be shifted in motion direction), indicates cross-modality effects from visually presented motion on tactile localization but not vice versa (Merz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…To fully understand human processing of time and space, multisensory studies are needed. It was already shown that cross-modality tau (Kawabe et al, 2008 ) and kappa (Bausenhart & Quinn, 2018 ) effects can be observed when temporal information is presented auditorily and spatial information visually. Also, research in related areas, for instance, on the representational momentum (the final location of a disappearing moving object is perceived to be shifted in motion direction), indicates cross-modality effects from visually presented motion on tactile localization but not vice versa (Merz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Compared to the previous studies on multimodal stimulation [25], [11], [12], each assessing only a specific incongruent condition, this study provides a wide overview, although on a preliminary base, of all the possible reciprocal influences between visual and tactile domains concerning time and space perception. This overview shows a general preeminent role of the visual domain on the tactile one, specially when they conflict [34]: in particular, regarding the time perception, the Kappa effect vanished in both the perceptual channels when the temporal illusion was provided in the tactile domain only (i.e., BIT).…”
Section: Discussionmentioning
confidence: 99%
“…Russo and Dell'Antonio [12], instead, were able to reproduce the tactile Tau effect exploiting the auditory Oppel-Kundt temporal illusion (i.e., a subdivided time interval is perceived longer than a non subdivided one), confirming that also an apparent temporal dilation can alter the perception of physical spaces. Finally, despite the usual prevalence of the auditory domain in the perception of time, Bausenhart et al [25] found a significant Kappa effect originated by a task-irrelevant visual stimulus on the estimation of auditory intervals duration.…”
Section: A Related Workmentioning
confidence: 94%
See 1 more Smart Citation
“…The Kappa effect elicited by the multiple modalities has received scarce attention. Bausenhart et al 14 found a significant Kappa effect originated by a visual stimulus on the estimation of auditory interval duration. The same authors were able to generate a time dilation by modulating the asynchrony between visual and auditory stimuli 15 .…”
Section: Introductionmentioning
confidence: 99%